Profile of multiple intelligences in the students of the University of Zulia - Mariotti, Luigina; Márquez, Jeanette; Sánchez, Marhilde (Omnia, 2024)
This study is related to Gardner’s (1985), theory of multiple intelligences, which considers that individuals have at least several intelligences (9) and are made up of a set of different abilities that are interrelated. The general objective was to determine the profile of multiple intelligences in students of the University of Zulia (LUZ); following the quantitative, descriptive approach, under a non-experimental and transversal design; applying a standardized instrument (MIDAS) supported by Gardner’s approaches (1985); to determine the profile of multiple intelligences. The results reflect that in the students of period I - 2022 of LUZ, three types of intelligence prevail; the first: intrapersonal intelligence, the second: linguistic intelligence and the third: interpersonal intelligence; where the first and the third transcend the traditional character of Intelligence as a process for solving problems; what does not happen in the second intelligence